The Relationship Between Intrapersonal Intelligence and Learning Motivation on Student Learning Outcomes in Biology Subjects - Rahmawati, Nadhya; Mustofa, Romy Faisal; Ardiansyah, Ryan (Universitas Lampung, 2023)
This research is a correlational study that aims to determine the correlation between intrapersonal intelligence and learning motivation on learning outcomes. The research sample was 55 students by saturated sampling technique. Data collection techniques used documentation and an intrapersonal intelligence questionnaire with 45 statement items and a learning motivation questionnaire with 32 statement items. Data were analyzed using statistical analysis of product moment correlation test, simple regression and multiple regression. The results of the study show that (1) there is a corellation between intrapersonal intelligence and learning outcomes with a correlation value of 0,351. (2) there is a correlation between learning motivation and learning outcomes with a correlation value of 0,400. (3) there is a correlation between intrapersonal intelligence and learning motivation on learning outcomes with a correlation value of 0,472. So it can be concluded that there is a positive correlation between intrapersonal intelligence and learning motivation on student learning outcomes.